2004
DOI: 10.1128/jb.186.12.3777-3784.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dissection of Escherichia coli Trigger Factor: Unraveling the Function of Individual Domains

Abstract: In Escherichia coli, the ribosome-associated chaperone Trigger Factor (TF) promotes the folding of newly synthesized cytosolic proteins. TF is composed of three domains: an N-terminal domain (N), which mediates ribosome binding; a central domain (P), which has peptidyl-prolyl cis/trans isomerase activity and is involved in substrate binding in vitro; and a C-terminal domain (C) with unknown function. We investigated the contributions of individual domains (N, P, and C) or domain combinations (NP, PC, and NC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 24 publications
11
90
0
Order By: Relevance
“…Consistently, when not associated with the ribosome, TFa does not display specific peptide binding in solution (26) and does not assist the refolding of denatured proteins (24). We therefore conclude that the observed TFa conformational change, which occurs upon association with the large ribosomal subunit and results in the exposure of a hydrophobic pocket, confers chaperone activity on TFa.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Consistently, when not associated with the ribosome, TFa does not display specific peptide binding in solution (26) and does not assist the refolding of denatured proteins (24). We therefore conclude that the observed TFa conformational change, which occurs upon association with the large ribosomal subunit and results in the exposure of a hydrophobic pocket, confers chaperone activity on TFa.…”
Section: Discussionmentioning
confidence: 52%
“…It was shown that TF can be crosslinked to an emerging nascent chain when bound to the ribosome (24). Furthermore, TF is known to delay the folding and͞or misfolding of nascent chains by recognizing hydrophobic regions in nascent polypeptides (25).…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli Ffh, FtsY, 4.5S RNA, and TF were expressed and purified using established protocols (76,77). Single cysteine mutations were introduced via Quikchange mutagenesis (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…The second TF domain (aa 149-245) carries a catalytic activity as a peptidyl-prolyl cis/trans isomerase (PPIase) and has homology to the FKBP (FK506 binding protein) type of PPIases. The contributions of this domain to TF's function in de novo folding of proteins is puzzling since mutations in this domain, either point mutations diminishing the catalytic PPIase activity or deletion of the entire domain, still display chaperone activity in vivo comparable to wild type TF [71,[77][78][79]. The C-terminal domain (aa 246-432), which constitutes nearly half of the TF protein, reveals no homology on the amino acid level to any other protein [80].…”
Section: In Vivo Role Of Tf In Protein Foldingmentioning
confidence: 99%
“…The C-terminal domain (aa 246-432), which constitutes nearly half of the TF protein, reveals no homology on the amino acid level to any other protein [80]. Deletion of this domain severely decreases TF chaperone activity in vitro and in vivo [71,77,78], indicating that this domain itself participates in substrate binding. Very recently, the crystal structure of E. coli TF [81][82][83][84], as well as that of an N-terminal TF fragment bound to Haloarcula marismortui 50S, were solved [81].…”
Section: In Vivo Role Of Tf In Protein Foldingmentioning
confidence: 99%